2009
DOI: 10.1063/1.3102095
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the Au(111)/methylthiolate interface: New insights from near-edge x-ray absorption spectroscopy and x-ray standing waves

Abstract: The local structure of the Au(111)(√3x√3)R30°-methylthiolate surface phase has been investigated by S K-edge near-edge X-ray absorption fine structure (NEXAFS) both experimentally and theoretically, and by experimental normal-incidence X-ray standing waves (NIXSW) at both the C and S atomic sites. NEXAFS shows not only excitation into the intramolecular * S-C resonance, but also into a * S-Au orbital perpendicular to the surface, clearly identifying the local S headgroup site as atop an Au atom.Simulations s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
40
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 31 publications
3
40
0
Order By: Relevance
“…19,21,22 The same configuration, including Au adatoms bonded to two RS-groups, has been named the "standard model" for close-packed methylthiolate self-assembled monolayers on Au(111), 23 as it has been found in several experimental and theoretical studies for this system. [24][25][26][27] Such bonds between two S atoms and a Au adatom appear due to low reactivity of Au atoms in the close-packed (111) surface, and are expected to be less likely in stepped or kinked surfaces, where undercoordinated Au atoms form significantly stronger bonds to S. Moreover, the strong steric repulsions associated with adsorption of longer molecules will result in grafting densities of the order of 1 nm −2 or less, 28 where it is unlikely that thiolate groups from two different molecules will bind to the same Au atom.…”
Section: Introductionmentioning
confidence: 99%
“…19,21,22 The same configuration, including Au adatoms bonded to two RS-groups, has been named the "standard model" for close-packed methylthiolate self-assembled monolayers on Au(111), 23 as it has been found in several experimental and theoretical studies for this system. [24][25][26][27] Such bonds between two S atoms and a Au adatom appear due to low reactivity of Au atoms in the close-packed (111) surface, and are expected to be less likely in stepped or kinked surfaces, where undercoordinated Au atoms form significantly stronger bonds to S. Moreover, the strong steric repulsions associated with adsorption of longer molecules will result in grafting densities of the order of 1 nm −2 or less, 28 where it is unlikely that thiolate groups from two different molecules will bind to the same Au atom.…”
Section: Introductionmentioning
confidence: 99%
“…RS-Au-SR complexes bonded to Au͑111͒ has been observed at different coverages by STM, 23 calculations of the infrared ͑IR͒ vibrational signatures match the experimental data, 24 simulations of the GIXRD maps 25 are in agreement with experiments and calculations for the RS-Au-RS structure compare favorably with sulfur K-edge near-edge x-ray absorption fine-structure ͑NEXAFS͒ measurement. 26 It has also been suggested that the RS-Au-RS structure might be consistent with normal-incidence XSW data. 26 In most cases, however, the experimental assignments are not conclusive.…”
Section: Introductionmentioning
confidence: 63%
“…26 It has also been suggested that the RS-Au-RS structure might be consistent with normal-incidence XSW data. 26 In most cases, however, the experimental assignments are not conclusive.…”
Section: Introductionmentioning
confidence: 63%
“…[416] This result follows directly from the Au 0 -thiyl nature of the surface and is opposite to that predicted if the surface was Au I -thiolate. Similarly, near-edge X-ray absorption fine structure (NEXAFS) measurements of SAMs [417] show electronic transitions to orbitals that are vacant in the Au 0 -thiyl description of the surface but already occupied in the Au I -thiolate description. [382] All DFT calculations show electronic structures of Au 0 -thiyl form, [415,[417][418][419][420][421][422][423][424][425][426] with the sulfur orbitals mixing with gold d-orbitals as predicted only by the Au 0 -thiyl description.…”
mentioning
confidence: 99%
“…[382] All DFT calculations show electronic structures of Au 0 -thiyl form, [415,[417][418][419][420][421][422][423][424][425][426] with the sulfur orbitals mixing with gold d-orbitals as predicted only by the Au 0 -thiyl description. [415,417,421,427] Often DFT publications report the structure as being Au I -thiolate, however, reflecting not the nature of the orbitals generated but rather the most commonly used descriptions in the field at the time. All chemical species involving Au-S bonds must show some degree of Au 0 -thiyl character and some degree of Au I -thiolate character as these two limiting valence forms mix via resonance in order to produce the ground and excited states of any system.…”
mentioning
confidence: 99%